The Influence of PAD, Inflation, Interest Rates on GRDP through Regional Financial Performance of South Sulawesi Province - Asmawati, Aqilah Nurfadillah H; Wahab, Abdul (ICOR: Journal of Regional Economics, 2024)
South Sulawesi's GRDP has experienced ups and downs in the last 5 years, namely 2018-2022, regional financial performance has experienced an unstable level of efficiency. Meanwhile, PAD, inflation and interest rates experienced ups and downs every year from 2018-2022. Therefore, this research is directed at analyzing PAD, inflation and interest rates in South Sulawesi Province between 2007-2022, and to understand their influence on GRDP and financial performance in the province. Using secondary data from the Central Statistics Agency and the Directorate General of Fiscal Balance, Ministry of Finance, South Sulawesi Province, this research applies multiple linear regression analysis using e-views 12. The results of this research show that the accepted hypothesis is a significant relationship between the independent variable and the dependent variable. The results of this research show that PAD has a significant effect on GRDP and regional financial performance, while inflation and interest rates do not have a significant effect on GRDP and regional financial performance.